Interval timing predicts impulsivity in intertemporal choice: combined behavioral and drift-diffusion model evidence. Issue 8 (17th November 2018) - Sharma, Sathya Narayana; Khan, Azizuddin
ABSTRACT: This study investigated the relationship between interval timing and impulsivity in intertemporal choice in a healthy population. A duration production task was used to assess interval timing. Choice impulsivity was assessed using a hypothetical money choice task. Results from 134 participants indicated that faster internal clock significantly predicted lower choice impulsivity. A subsequent drift-diffusion model analysis of the behavioural data revealed that in the sub-group of relatively farsighted participants, faster internal clock predicted consideration of more information before making a choice, which in turn was associated with lower choice impulsivity. In the sub-group of relatively impatient participants too, faster internal clock predicted consideration of more information, but which in turn was associated with higher choice impulsivity. It is concluded that among relatively farsighted individuals in a normal population, faster internal clock favours a more deliberate processing of the options at hand, thus eliciting less impulsive choices.